Analisis Perlindungan Hukum Konsumen pada Fitur Paylater di Aplikasi Gojek Berdasarkan Peraturan Otoritas Jasa Keuangan Nomor 77/POJK.01/2016 - Salim, Marsela; S, Sepriyadi Adhan; Zazili, Ahmad (JUSTICIA SAINS - Jurnal Ilmu Hukum, 2025)
Legal protection for consumers using the PayLater feature on the Gojek app has become an important issue amid the development of fintech services in Indonesia. This feature offers convenience in transactions with a deferred payment system, but it also carries risks such as unclear information, misuse of personal data, and unethical collection practices. According to the Financial Services Authority (OJK) Regulation No. 77/POJK.01/2016, legal protection includes transparency of information, the legality of the service provider, protection of personal data, electronic agreements, and professional debt collection processes. Consumers also have access to dispute resolution mechanisms, such as the Consumer Dispute Resolution Body (BPSK), Alternative Dispute Resolution (ADR), courts, complaints to the OJK, and internal complaint mechanisms. Although existing regulations provide a strong legal protection framework, further improvements in education, transparency, and oversight are still needed to ensure consumer rights are better safeguarded. Collaboration between regulators, operators, and the public is key to creating a safe and sustainable fintech ecosystem